Where do I begin? Elementary Teacher Candidates’ Understanding and Perceptions of Media Literacy Education - Ahn, Claire; Beach, Pamela; Minuk, Alexandra (Language and Literacy / Langue et littératie, 2025)
With advancements in technology, more children are engaging with media at younger ages. While elementary teacher candidates recognize the importance of media literacy instruction, and the willingness to learn more to better support their future students, attention to the overall implementation of media literacy education in teacher education programs appears to be limited. This paper shares survey data of elementary teacher candidates’ perceptions of and experiences with media literacy instruction and the kinds of resources they have been introduced to in their program that (re)highlight the need for better programming and support in relation to media literacy education.